2022
DOI: 10.1021/acs.estlett.2c00259
|View full text |Cite
|
Sign up to set email alerts
|

Complementing RNA Detection with Pharmaceutical Monitoring for Early Warning of Viral Outbreaks through Wastewater-Based Epidemiology

Abstract: Wastewater-based epidemiology using viral nucleic acids to predict community viral outbreaks has many challenges, including differences in viral shedding of infected individuals and interference from the wastewater matrix. In this study, we demonstrate that monitoring pharmaceutical residues in untreated sewage provides complementary information that correlates with future occurrences of viral outbreaks. We monitored 63 pharmaceutically active compounds, including antivirals used to treat COVID-19 and influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 63 publications
0
8
1
Order By: Relevance
“…Here, the estimation of the number of absent workers due to COVID-19 infections was performed via a Poisson regression model. Other studies also have shown the trends and strong correlation of clinical data with the SARS-CoV-2 RNA abundance in wastewater on a weekly basis (Wartell et al 2022; Fahrenfeld et al 2022; Halwatura et al 2022; Krivoňáková et al 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Here, the estimation of the number of absent workers due to COVID-19 infections was performed via a Poisson regression model. Other studies also have shown the trends and strong correlation of clinical data with the SARS-CoV-2 RNA abundance in wastewater on a weekly basis (Wartell et al 2022; Fahrenfeld et al 2022; Halwatura et al 2022; Krivoňáková et al 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Over the past decade, wastewater surveillance in Europe, Australia, and Canada has proven successful in providing large-scale spatiotemporal data sets on population-level consumption of opioids, amphetamines, cocaine, cannabis, and other substances of concern. Wastewater surveillance in these regions has also demonstrated its potential to function as a warning system for detecting the emergence of new psychoactive substances despite their constantly changing profiles and lower prevalence of use compared to traditional drugs of abuse. , To date, most WBE studies in the U.S. have focused on assessing the mass loads and/or consumption rates of priority opioids and stimulants, , therapeutic drugs, , and lifestyle chemicals, , although recent efforts have sought to investigate the occurrence of emerging psychoactive substances. , Taken together, these studies have gathered important baseline data on substance consumption by diverse communities in the U.S. and underscored the opportunity to leverage ongoing or planned wastewater surveillance initiatives in supporting substance use assessment. From a practical standpoint, pivoting current wastewater surveillance initiatives, particularly those with broad spatiotemporal sampling regimes, to incorporate substance use assessment requires a phased approach to evaluate operational feasibility before the programs are scaled to reach their full potential.…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater surveillance in these regions has also demonstrated its potential to function as a warning system for detecting the emergence of new psychoactive substances despite their constantly changing profiles and lower prevalence of use compared to traditional drugs of abuse. 12 , 13 To date, most WBE studies in the U.S. have focused on assessing the mass loads and/or consumption rates of priority opioids and stimulants, 14 , 15 therapeutic drugs, 16 , 17 and lifestyle chemicals, 18 , 19 although recent efforts have sought to investigate the occurrence of emerging psychoactive substances. 13 , 20 Taken together, these studies have gathered important baseline data on substance consumption by diverse communities in the U.S. and underscored the opportunity to leverage ongoing or planned wastewater surveillance initiatives in supporting substance use assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its use during the COVID-19 pandemic, the predicted concentration of CQ in domestic wastewater was up to 857 ng/L . In a study conducted in 2021, the concentration of CQ in wastewater from four WWTPs in western New York was up to 33 μg/L . The extensive- and overuse of CQ during the COVID-19 pandemic has resulted in a significant release of CQ via WWTP effluents, presenting a risk to the recipient aquatic environment. , Moreover, the use of chlorine disinfection increased during the COVID-19 pandemic to help prevent the secondary spread of SARS-CoV-2 through wastewater pipes and WWTPs .…”
Section: Introductionmentioning
confidence: 99%